Pengislaman Mojokerto pada Masa Majapahit: Peran Syekh Jumadil Kubro dan Pengaruhnya Pra Hingga Pasca Keruntuhan - Almas Wilda Pradnya Megananda; Rasmuin (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2024)
The Islamization of Mojokerto by Sheikh Jumadil Kubro: From Pre to Post-Java War 1820-1830 examines the pivotal role of Sheikh Jumadil Kubro in the spread of Islam in Mojokerto, East Java. This research traces the historical journey from the initial introduction of Islam to its establishment as a dominant cultural force, particularly during the turbulent era surrounding the Java War. By analyzing historical records, local traditions, and oral histories, the study highlights the strategic methods employed by Sheikh Jumadil Kubro in fostering Islamic beliefs. It also explores the impact of the Java War on the religious and social dynamics of Mojokerto, providing insights into the broader implications for the spread of Islam in Indonesia. The findings underscore the significance of religious leaders in shaping societal changes and contribute to a deeper understanding of Indonesia's Islamic heritage.